Parent-Reared Bobwhite Survival in the Texas Rolling Plains - Mark A. Thomas; C. Brad Dabbert (National Quail Symposium Proceedings, 2017)
Considerable research has been accomplished over the past 6 decades on the possible reasons for decline in the northern bobwhite (Colinus virginianus), henceforth known as the bobwhite. Restoring or restocking bobwhite populations by augmentation in areas that once held significant numbers has been a focus for many wildlife agencies and managers. Three main methods for augmentation of bobwhites currently exist: release of pen-raised birds, release of juvenile birds reared by Surrogator®, and translocation of wild bobwhites from one area to another. Of these 3 methods, only translocation has accomplished the goal of reestablishing bobwhite populations. Recently a new model developed by Tall Timbers Research Station in Tallahassee, Florida, USA, has successfully produced parent-reared bobwhite chicks from wild strain, which are raised by a surrogate parent in a simulated wild habitat environment. These birds have been released into the southeastern United States and successfully established new bobwhite population in areas of restored habitat. We designed a study to determine the viability of this rearing and release method for restoring depleted bobwhite populations in the semiarid, Rolling Plains of Texas. One hundred fifty nine radiomarked, parent-reared bobwhites were released in 2013–2014 on 8 ranches. One hundred five radiomarked, parent-reared bobwhites were released in 2014–2015 on 6 ranches. The survival rates were low for both years of the study with only 4 radiomarked birds surviving the first year and no birds surviving the second year. An apparent lack of predator-avoidance skills appears to be responsible for the high mortality rates that we estimated.
Keywords: anti-predator behavior; colinus virginianus; northern bobwhite; parent-reared; population augmentation